W oczekiwaniu na wytęsknione i "pocieszne nowiny" z 1621 roku. Zapomniany "prolog" do "Diariusza" Prokopa Zbigniewskiego = Waiting for longed and "glad tidings" in 1621. Forgotten "prologue" to "Diary" by Prokop Zbigniewski - Sztyber, Radosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper is an attempt of both presenting and re-issue (with commentaries) XVII century Polishwritten relic (edited especially in prose). It is just a short preface - rather unknown - introductingto "Diary" by Prokop Zbigniewski. The "prelude" announces the report (day by day) of the battle atKhotin (Chocim) prepared by the eyewitness and participant of warfare near the Dniester Riverbetween Poland and Ottoman empire in 1621. The motifs and thoughts contained in the "prologue"reveal an author ? educated, well-read and waiting for the newest and actual information.
Keywords: Zbigniewski, Prokop; literatura polska - historia - 10-16 w.